The language of war monuments - Abousnnouga, Gill; Machin, David 1966- (Bloomsbury advances in semiotics, 2013)
This book analyses war monuments by developing a multimodal social-semiotic approach to understand how they communicate as three-dimensional objects. The book provides a practical tool-kit approach to how critical multimodal social semiotics should be done through visual, textual and material analysis. It ties this material analysis into the social and political contexts of production. Using examples across the 20th and 21st century the book's chapters offer a way of analysing the way that monument designers have used specific semiotic choices in terms of things like iconography, objects, shape, form, angularity, height, materials and surface realisation to place representations of war in public places across Britain.